Oceanography in the days of sail - Jones, Ian; Jones, Joyce (Sydney : Hale & Iremonger, 1992)
Only in the last one hundred years has oceanography been a recognized science. Long before that, however, in maritime societies, the natural history of the seashores had aroused the interest and curiosity of those who lived near the sea and the behavior of the coastal waters upon which they sailed and fished had a very practical importance. Scientific interest in the sea dates back at least to Greek and Roman times. Tidal behavior, in particular, being very visible, became an early subject of interest and observation. History records the effect of this insufficiently documented oceanographic factor in the military activities of both Alexander the Great and Julius Caesar. As observation and experimentation increased in importance as a source of knowledge, and the study of 'natural history' advanced and subdivided into separate sciences, the study of the sea advanced within each of these sciences. When the European communities, in particular, sent their sailing vessels further and further afield, the curiosity of the scientifically inclined found an ever enlarging source of nourishment in the observations that were now possible of the wider oceans and distant seas. Supported by those with practical goals of improving navigation and reducing passage risk, the inquisitive were able to build a description of the oceans. With improved instrumentation, and the capacity to measure and record came the interest in the physical aspects of oceanic behavior and the beginnings of the science of physical oceanography.
1. Terra Australis Incognita -- 2. In the Wake of Laperouse -- 3. The Curiosity of the Europeans -- 4. Pax Britannica -- 5. America's Bid for Status and Enlightenment --6. Oceanography: The New Profession -- 7. An Australian National Program.
Includes bibliographical references and index.